Cisplatin-resistant prostate cancer model: Differences in antioxidant system, apoptosis and cell cycle - Gumulec, Jaromir; Balvan, Jan; Sztalmachova, Marketa; Raudenska, Martina; Dvorakova, Veronika; Knopfova, Lucia; Polanska, Hana; Hudcova, Kristyna; Ruttkay-Nedecky, Branislav; Babula, Petr; Adam, Vojtech; Kizek, Rene; et al. (International journal of oncology, 2014)
Differences in the antioxidant system, apoptotic mechanism and in cell cycle between prostatic cell lines could partially elucidate the development of cisplatin resistance. The aim of this study was to identify the most characteristic parameter for a particular cell line and/or a particular cisplatin treatment using a general regression model and to assess whether it is possible to use measured parameters as markers of cisplatin resistance. This study integrates the results of viability, antioxidant, flow cytometric and quantitative PCR assays in order to characterize the resistance of prostate cancer to cisplatin. Cell growth using metabolic- (MTT) and impedance-based assays, the expression of key cell death signaling proteins (p53, Bax and Bcl-2), cell cycle, activity of antioxidant system-related proteins (superoxide dismutase, glutathione peroxidase, glutathione reductase and metallothionein) and free radical scavenging capacity assays [free radicals (FR), ferric reducing antioxidant power (FRAP), ABTS] were analyzed in the cell lines 22Rv1, PC-3 and PNT1A with respect to rising concentrations (0-150 µM) and different length of cisplatin treatment (12-72 h). The non-functional-p53 PC-3 cell line showed decreased BAX (p<0.05) and, in contrast to PNT1A and 22Rv1, no cisplatin-induced effects on cell cycle. All cell lines showed increasing levels of free radical scavenging activity by ABTS, FRAP and FR assays in a time- and dose-dependent manner (r>0.76 at p<0.001 for ABTS, FRAP and FR at p<0.001). PC-3 showed increased (p<0.05) levels of free radical scavenging activity by ABTS and FR methods. These findings, together with significantly elevated MT, decreased p53 and Bax indicate PC-3 to be cisplatin-resistant. The differences in the antioxidant system and apoptotic mechanisms in PC-3 cells may elucidate the development of cisplatin resistance and indicate that this cell line may be further studied as a model of cytostatic resistance.
Keywords: Male; Drug Resistance, Neoplasm; Tumor Suppressor Protein p53; Cell Proliferation; Prostatic Neoplasms; chemorezistence; Humans; cisplatina; antioxidancia; mužské pohlaví; buněčný cyklus; proliferace buněk; Antioxidants; Cell Cycle; Cell Line, Tumor; nádorové buněčné linie; apoptóza; nádory prostaty; lidé; Cisplatin; Signal Transduction; nádorový supresorový protein p53; Apoptosis; signální transdukce